Pharmacological impact of microRNAs in head and neck squamous cell carcinoma: Prevailing insights on molecular pathways, diagnosis, and nanomedicine treatment - Bhattacharjee, Bedanta; Syeda, Ayesha Farhana; Rynjah, Damanbhalang; Hussain, Shalam M.; Chandra Bora, Shekhar; Pegu, Padmanath; Sahu, Ram Kumar; Khan, Jiyauddin (Frontiers in Pharmacology, 2023)
Head and neck squamous cell carcinoma (HNSCC) is a disease that most commonly produce tumours from the lining of the epithelial cells of the lips, larynx, nasopharynx, mouth, or oro-pharynx. It is one of the most deadly forms of cancer. About one to two percent of all neo-plasm-related deaths are attributed to HNSCC, which is responsible for about six percent of all cancers. MicroRNAs play a critical role in cell proliferation, differentiation, tumorigenesis, stress response, triggering apoptosis, and other physiological process. MicroRNAs regulate gene ex-pression and provide new diagnostic, prognostic, and therapeutic options for HNSCC. In this work, the role of molecular signaling pathways related to HNSCC is emphasized. We also provide an overview of miRNA downregulation and overexpression and its role as a diagnostic and prognostic marker in HNSCC. In recent years, miRNA nano-based therapies for HNSCC have been explored. In addition, nanotechnology-based alternatives have been discussed as a promising strategy in exploring therapeutic paradigms aimed at improving the efficacy of conventional cytotoxic chemotherapeutic agents against HNSCCs and attenuating their cytotoxicity. This article also provides information on ongoing and recently completed clinical trials for therapies based on nanotechnology.